DNA Fingerprinting of Theobroma Cacao - Basherudin, Norlia (1998)
Traditionally, the characterisation of Theobroma cacao is based on morphological characteristics and geographical distribution. Three major groups have been identified, namely, eriolla, Forestero and Trinitario (Wood, 1985). Crosses between these three groups have constitute the major breeding strategies used during the last few years. Currently, large numbers of cocoa clones derived from these crosses have been introduced in cocoa plantations. Two different techniques, Random Amplified Polymorphic DNA (RAPD) with random primers and Restriction Fragment Length Polymorphism (RFLP) using universal probes, has been investigated as a mean to differentiate 12 local cocoa clones with 1 imported clone as a comparison. 40 primers have been used to amplify genomic DNA from 13 cocoa clones. Agarose and acrylamide gel electrophoresis used to separate the RAPD products were further stained with ethidium bromide and sliver nitrate, respectively. NTSYS-PC computer programme was used to analyse the RAPD data. Meanwhile, two types of probe were used in RFLP study, viz M13 phage DNA and a fragment from a RAPD product. The RAPO technique was found to be able to differentiate between local cocoa clones. Combining the result with UPGMA analysis, 13 tested clones were determined to fall Into 3 main clusters. A band map has been formed as a future source of reference to determine the best combination of markers to differentiate two or more clones. M 13 DNA, as a probe in the RFLP study, failed to give a consistence results in differentiating cocoa clones. An RAPD product, as a probe however was able to hybridise to few digested genomic DNA fragments. This indicates that the product is truly amplified fragment and was confirmed to be mid-repetitive. However the probe did not produce any polymorphic bands between the clones.